1995
DOI: 10.1159/000188675
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Renal Failure: A Comparison of Acute Continuous Hemodiafiltration and Conventional Dialytic Therapy

Abstract: It is unknown whether continuous renal replacement techniques result in diminished morbidity and mortality when compared to conventional dialytic techniques. To investigate this issue a previously described, retrospectively studied group of critically ill patients with severe acute renal failure treated by conventional dialysis (CD) was compared to a prospectively studied group of similar patients treated by acute continuous hemodiafiltration (ACHD). A combined retrospective and prospective clinical and labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(34 citation statements)
references
References 15 publications
0
32
0
2
Order By: Relevance
“…Rationale Although numerous nonrandomized studies have reported a nonsignificant trend toward improved survival using continuous methods [488][489][490][491][492][493][494], two meta-analyses [495,496] reported the absence of significant differences in hospital mortality between patients who receive CRRT and intermittent RRT. This absence of apparent benefit of one modality over the other persists even when the analysis is restricted to RCTs [496].…”
Section: We Suggest Against the Use Of Rrt In Patients With Sepsis Anmentioning
confidence: 99%
“…Rationale Although numerous nonrandomized studies have reported a nonsignificant trend toward improved survival using continuous methods [488][489][490][491][492][493][494], two meta-analyses [495,496] reported the absence of significant differences in hospital mortality between patients who receive CRRT and intermittent RRT. This absence of apparent benefit of one modality over the other persists even when the analysis is restricted to RCTs [496].…”
Section: We Suggest Against the Use Of Rrt In Patients With Sepsis Anmentioning
confidence: 99%
“…The causes of AKI were variable, with the most common causes being reported as sepsis (10,15,17,18,22,25,(27)(28)(29)(30)(33)(34)(35)(36)(37), prerenal causes or hypovolemia (6,17,22,26,28,30,32,(35)(36)(37), cardiac failure (10,18,22,30,35,36), postsurgery (10,18,19,26,31,35), and nephrotoxic agents (22,26,35,36). Mortality was reported at hospital discharge (6,15,23,35), at 30 days (10,17,18,27), or not specified. Mortality at the last reported follow-up was used in the analysis.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…Four studies (19,20,31,32) did not report parameters that indicate the risk profile of the cohort, such as the proportion of septic and ICU patients. Only seven studies reported an illness severity score (10,15,18,25,27,29,37).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 2 more Smart Citations